Attitude, Social Norms, Perceived Behavioral Control, Past Behavior, and Habit in Explaining Intention to Consume Fish in Vietnam - Ho, Huy Tuu (University of Economics Ho Chi Minh City, 2023)
The purpose of this study is to discuss and test the direct and moderating effects of attitudes, social norms, perceived behavioral control (PBC), past behavior, and habit strength in explaining Vietnamese consumers’ intention to consume fish. In addition to a data set of 466 consumers in a coastal province in Central Vietnam and structural equation modelling, a model development strategy with six nested models is used to test hypotheses. Results indicate that attitude, social norms, and PBC have a positive effect on intention. Both past behavior and habit strength have a significantly positive influence on intention and considerably increase the explained variance of intention. In particular, the results also indicate that habit strength, past behavior, and social norms negatively moderate the impact of attitudes on intention. All of these findings emphasize the importance of past behavior and habit strength as well as interactions within the theory of planned behavior in explaining intention to consume fish in Vietnam.